Perbuatan Melawan Hukum Oleh Pemerintah Dalam Perspektif Keperdataan Dan Administrasi Negara - Irfan Syafar; Herman; Firmansyah (Fakultas Hukum, Universitas Sawerigading Makassar, 2025)
Government actions can have implications for two legal conditions, namely civil and state administration aspects, which allow the government, under certain conditions, to commit unlawful acts as a legal subject (Onrechtmatige Daad) and unlawful acts as an organization (Onrechtmatige Overheidsdaad). Specifically, this study aims to examine and analyze unlawful acts by the government in the context of civil and state administration. It should provide a comprehensive description of government actions as unlawful acts when the government acts as a legal subject and plays a role as a state institutional organization, thereby distinguishing the actions taken by the government relevant to their legal consequences. This research is descriptive and analytical in nature, intended to provide a substantial overview of the focus of the research by utilizing legal norms, basic theories, and the principles of Good Governance as a basis for crystallizing a valid argument so as to answer the research questions. This study shows that unlawful acts by the government must be understood integrally through two main perspectives: civil law and administrative law. From a civil law perspective, the assessment of unlawful acts is based on the fulfillment of the elements of action, fault, loss, and causality. Meanwhile, from the perspective of administrative law, the assessment is carried out through the parameters of authority, procedure, substance, and the general principles of good governance. This study concludes that unlawful acts by the government are a complex legal phenomenon involving elements of civil and administrative law. The government, as a subject of public law, is obliged to act within the corridor of applicable legal norms, and if it violates the elements of unlawful acts, it can be held civilly liable for compensating the losses suffered by citizens. An inclusive juridical approach to these unlawful acts, which considers not only formal legal aspects but also normative and social aspects, is essential to ensure substantive justice and accountability in government administration